DI-066 Permeation enhancers: Excipients to be considered in topical formulations with systemic adverse effects. (14th February 2016) - Sousa, AL; Palmeira-de-Oliveira, A; Morgado, M; Martinez-de-Oliveira, J; Palmeira-de-Oliveira, R
Abstract : Background: Most topical dermatologic preparations are presented as semisolids meant to be locally active. Although the stratum corneum acts as the rate limiting barrier, variable systemic adverse effects may occur due to drug permeation through the skin. 1 Formulations often include penetration enhancers either intentionally selected for this function or as excipients with other purposes which end up by facilitating the percutaneous absorption of the active ingredients. Purpose: To review the most frequently used permeation enhancers in topical preparations in view of their potential role in promoting systemic adverse effects. Material and methods: Bibliographic search in PubMed, Google Scholar and Science Direct using the terms 'permeation enhancer', 'skin permeation', 'systemic absorption of topical drugs'. Results: Occlusive dosage forms, such as ointments, may promote drug permeation by increasing the hydration and temperature of the stratum corneum. Concerning excipients, several mechanisms have been identified: skin hydration increase (urea); reduction of the permeation barrier (amides, such as azone, used as solvents and that act through drug partitioning improvement); substances which pass through the stratum corneum (pyrrolidones, which affect hydrophilic and lipophilic drugs; surfactants, especially anionic or cationics, used as emulsifiers; small peptides which act by stabilising structural proteins in the skin; modifiers of the stratum corneum: essential oils, terpenes and terpenoids; fatty acid esters: isopropyl myristate, which may promote drug solubility in the skin); sulphoxides, such as DMSO; alcohols, fatty alcohols and glycols: particularly ethanol which can increase drug solubility and extract some of the lipid fraction from the stratum corneum. Conclusion: The effectiveness and safety of dermatologic therapies depend on both the active drug and the properties of the vehicle. Identification of permeation enhancers included in topical preparations may be useful for hospital pharmacists in identifying and understanding their potential systemic adverse effects. References and/or Acknowledgements: Chang RK, Raw A, Lionberger R, et al . Generic development of topical dermatologic products: formulation development, process development, and testing of topical dermatologic products. Aaps J 2013;15:41-52 No conflict of interest.